Engaging Learners Through Emerging Technologies International Conference on ICT in Teaching and Learning, ICT 2012, Hong Kong, China, July 4-6, 2012. Proceedings - Li, Kam Cheong; Wang, Fu Lee.; Yuen, Kin Sun.; Cheung, Simon K. S.; Kwan, Reggie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the International Conference on ICT in Teaching and Learning, ICT 2012, held in Hong Kong, China, in July 2012. The 19 revised full papers presented were carefully reviewed and selected from numerous submissions. They explore the use of information technology to improve learning and teaching and showcase innovative pedagogical practices. The papers are organized in topical sections on the construct of student engagement and the applications of ICT; emerging pedagogies through ICT; applications of ICT in teaching and learning; research/case studies on ICT in engaged learning; and finally three papers on open textbooks, which address the current problems with conventional textbooks in Hong Kong.
Keywords: Computer science; Computer Communication Networks; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Computer Communication Networks; User Interfaces and Human Computer Interaction; Information Storage and Retrieval